Dampak Pencemaran Perairan Danau Bandar Kayangan Pekanbaru Terhadap Kelulushidupan dan Pertumbuhan Benih Patin Siam (Pangasius hypothalamus) Di Instalasi Budidaya Air Tawar Rumbai - Nurmayani Nurmayani; Sukendi Sukendi; Thamrin Thamrin (Berkala Perikanan Terubuk, 2015)
This research was conducted on October-December 2013, at Freshwater Culture Installation of Fisheries and Marine Department of  Riau Province and Bandar Kayangan Lake,  Lembah Sari village subdistrict Rumbai Pesisir Pekanbaru city Riau Province. The research aimed to analyze the water quality condition of Bandar Kayangan lake and determine the impact on  survival and growth of Catfish (Pangasius hypothalamus) fry. The method used is an experimental method by observing and measuring  sample directly on rearing cages measure 1x1x1 m. Catfish fries were stocked at the two weeks on age with the number ( 50 fries ) and  3 months time of rearing. Three units of cages were placed at each station that has been determined  and  Rumbai Freshwater Cultured Installation pond as control. The datas analyzed by descriptively and statistically, the descriptive analysis performed on physical and chemical parameters of water based on PP No. 82 year 2001 and was associated with the growth and survival of catfish fingerlings. Statistical analysis was using Analysis of Variance (ANOVA) and completely randomized design (CRD) with treatment of 3 times repetition. Growth and survival of catfish fingerlings on each station were quite well where the average growth of absolute weight between 35.43-36.20 grams, the average  growth rate of daily weight between 5.602-5.782%, the average of absolute growth in length between13,61-14.10 cm, the average of daily growth in length between 2.285 - 2.321% and the survival rate between 56-79%.